Roots or routes: A case for vertical farming allotments in Dunoon quarry - Madyibi, Nwabisa (School of Architecture, Planning and Geomatics, 2018)
This dissertation departs with an enduring interest in the social Milieu and the future projections of the fringes of South African major cities, specifically Cape Town, as urbanization broadens, transforms and makes the edge more complex. This document analyses this phenomenon in Dunoon Township and presents a case for vertical allotment farming in this context. The research, looks at this phenomenon as a narrative of land ownership in its most physical depictions, such as the story of the ownership of land to reap resources as the physical phenomenon of an abandoned quarry. This project acknowledges the danger and light treading around contentious environments, such as townships, which seem to create architecture that aggravates protest and vandalism, but chooses to counteract the pervasive 'headline-ing' of these areas by showing a township, Dunoon, as quotidian. This document does this by engaging with the life around the edge of the oldest quarry in the Durbanville Hills area - Once a source of great benefit and value to its immediate environment - now a fenced off cesspit for crime and superstition. An empathetic attitude towards considering material developed within the immediate environment to create value, as opposed to sourcing it from outside, is a founding precept for the design endeavour. The project can be described as a process which began by understanding the stagnant water within the basin of the quarry, what systems already exist to bring value to the urban fabric, and how the water can be best used in its mundane life. Beauty, viewed through the lens of this document, is something that brings undeniable usefulness to an area. That is the intervention of a wasted public space with rancid polluted water into clean usable water for a community suffering crippling rates of water shortage and cut-offs. It aims to put permaculture ideals into use by routing the stagnant water and making it into a system that consistently cleans itself over time. Routed water embeds a logic that becomes the catalyst for the fulfilment of a bio-inspired future -of which I emphatically advocate. This dissertation seeks to create an intervention which should encourage a new relationship with water in Dunoon. It is through a gathering of found program; farmers, NGO facilitators, walkers, joggers without tracks, children without playgrounds, women without laundry water tipping points, that the community is brought together in the water world of Dunoon quarry.